Evolution of the Unified State Exam and its Effect on Students’ Mathematical Preparation - A. S. Kotyurgina; E. I. Fedorova; V. B. Nikolaev; Yu. B. Nikitin (Образование и наука)
Introduction. The current long-term decline in the level of Russian school mathematics education is confirmed by the international research, the results of the international mathematical Olympiads for schoolchildren, the results of school final exams and university admission tests, and the unsatisfactory quality of training of first-year students. Teachers-mathematicians and many scientists tend to associate the lack of students’ mathematical knowledge with the introduction of the Unified State Exam (USE or EGE - high school final and university entrance exam taken upon completion of the 11th form) in Russia.The aims of the present research are the following: to identify the patterns in inter-annual changes in the assignments of the EGE in mathematics and to discuss the content and results of this exam for the last 15 years through the example of school graduates’ certification in the Omsk region.Methodology and research methods. The research was carried out on the basis of a systematic approach, using statistical and comparative retrospective analysis methods.Results and scientific novelty. The authors of the current publication examined the dynamics of transformation of the content of the final school exam in mathematics after the introduction of the EGE, evolution/involution of the tasks included in the exam and the influence of these processes and the proposed control and measuring materials (KIMs) on the quality of mathematical knowledge of potential university students. The attention of the authors was focused primarily on the assignments of the EGE, which require detailed, informed solutions and answers (the assignments, which were combined in tests before 2015 under the title “Part C”). The comparison of similar tasks at the traditional final examination at secondary school in 2000 and the written entrance examination of one of the Omsk universities of the same year with the assignments of the specialised EGE-2019 allowed the authors to reveal strong negative tendencies in mathematical training of schoolchildren. The graduates of general education institutions demonstrate the same modest gains in the EGE algebraic tasks from year to year. Although, the tasks are permanently simplified and do not differ in variety. On the contrary, geometric tasks are brought to a high-level, and, therefore, such tasks are not well solved by examinees. However, due to the non-linear rating scale, it is not necessary to do these tasks, as well as some other tasks involving a detailed solution. Without completing such tasks, it is now quite feasible for many students to get the certain number of points to enroll in the university, where the specialised EGE in mathematics is accepted as an entrance exam. But even a significant reduction of the level of assessment of satisfactory knowledge without good teachers, a carefully designed school curriculum and quality textbooks do not give rural school graduates a chance to obtain higher education and move up the social ladder.Practical significance. The results of this research can be used by the authors of KIMs to change and update the assignments of the Unified State Exam, and also by school teachers, lecturers at the courses and methodologists to change the focus of training.